(untitled) (Journal of history, 2022)
Ethnic interaction in the Turkestan region has its own characteristics, as it affects the demographic and stable socio-economic development and the state of the region. The social activity of the new generation of Kazakh youth and its ethno-political identification represents a new level of development of the population of Kazakhstan as a whole. The attitude of ethnic groups to the development of the state structure and social processes, interethnic relations, language policy and religion, socio-demographic and cultural development of the indigenous population and other ethnic groups in the country, the involvement and contribution of ethnic groups in the construction of a democratic country lead researchers to analyze the activities of ethnic groups and their interaction, as well as the identification and eradication of negative factors that have a direct attitude to national development. The results of the research of the staff of the scientific center “History and Ethnology”, a survey of focus groups, respondents give an answer to some questions of the interaction of ethnic groups in the Turkestan region. During the survey, some discrepancies were also revealed on the issues of infringement of rights, employment, religious tolerance and religion.